Functional Role of p38 Mitogen Activated Protein Kinase in Platelet Activation induced by a Thromboxane A2 Analogue and by 8-iso-prostaglandin F2α - Minuz, Pietro; Gaino, Stefania; Zuliani, Valeria; Tommasoli, Rosa Maria; Benati, Donatella; Ortolani, Riccardo; Zancanaro, Carlo; Berton, Giorgio; Santonastaso, Clara Lechi (Thrombosis and Haemostasis, 2002)
We investigated similarities in the signaling pathways elicited by the F2 isoprostane 8-iso-PGF2α and by low doses of U46619 to induce platelet activation. Both 0.01-0.1 µmol/L U46619 and 0.01-1 µmol/L 8-isoPGF2α triggered shape change and filopodia extension, as well as adhesion to immobilized fibrinogen of washed platelets. At these doses the two platelet agonists failed to trigger secretion and aggregation, which were however induced by higher doses of U46619 (0.1-1 µmol/L). SB203580 (1-10 µmol/L), a specific inhibitor of the p38 mitogen activated protein (MAP) kinase blunted platelet shape change and adhesion induced by 0.05-1 µmol/L 8-iso-PGF2α and by 0.01 µmol/L U46619. These platelet responses were also inhibited by 20 µmol/L cytochalasin D, an inhibitor of actin polymerization, and 50 µmol/L piceatannol, an inhibitor of the Syk tyrosine kinases. Both 8-iso-PGF2α and U46619-induced p38 MAP kinase phosphorylation in suspended platelets and this was inhibited by piceatannol, indicating that Syk activation occurs upstream p38 MAP kinase phosphorylation. These findings suggest that the signaling pathway triggered by both 8-iso-PGF2α and low concentrations of U46619 to induce platelet adhesion and shape change implicates Syk, the p38 MAP kinase, and actin polymerization.
Keywords: Platelet; shape change; adhesion; p38MAP kinase; 8-iso-PGF2β; U46619; fibrinogen receptor; piceatannol; Syk; electron microscopy